The Economics of English Proficiency in Global Labor Markets: A Systematics Review - Alia Rahmi Laila Safitri; Annisa Mutiara Fahmadira; Feby Puspitasari (Proceedings Law, Accounting, Business, Economics and Language, 2025)
This study examines the economic value of English proficiency in global labor markets and its role as human capital for career advancement. English has become essential for accessing international job opportunities, higher wages, and digital workplace participation in today's interconnected economy. The research analyzes workers across different countries, focusing on immigrants, graduates, and professionals in various sectors, building on theoretical work by Chiswick and Miller (1995) and recent digital economy scholars. The study covers diverse geographical contexts including developed economies (UK, US) and developing countries (China, India, South Africa), showing consistent patterns globally. The research spans from foundational studies in the 1990s to recent digital transformation research, addressing current remote work trends and technological changes. Using systematic literature review methodology with Miles and Huberman's (2014) qualitative data analysis approach, researchers collected information from international academic databases including Scopus, Web of Science, and others. Results show English proficiency provides significant wage advantages, ranging from modest gains in developed countries to over 50% increases in developing economies. Benefits are highest in international business, technology, and knowledge-based sectors. The digital economy amplifies these advantages, making English increasingly crucial for remote work and global economic participation.